2000
DOI: 10.1016/s0006-3495(00)76546-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Generation of Nonarbitrary Membrane Models Reveals Lipid Orientational Correlations

Abstract: This report addresses the following problems associated with the generation of computer models of phospholipid bilayer membranes using molecular dynamics simulations: arbitrary initial structures and short equilibration periods, an Ewald-induced strong coupling of phospholipids, uncertainty regarding which value should be used for surface tension to alleviate the problem of the small size of the membrane, and simultaneous realization of both order parameters and the surface area. We generated a computer model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 101 publications
10
56
0
Order By: Relevance
“…Within the same distance in the DMPC^Chol bilayer, there are 3.4 alkyl chains and 1.5 Chol molecules. Similar RDFs to those discussed above were obtained for a DMPC membrane parametrised in the all-atom approximation [26].…”
Section: Chain Packing In the Hydrophobic Coresupporting
confidence: 78%
“…Within the same distance in the DMPC^Chol bilayer, there are 3.4 alkyl chains and 1.5 Chol molecules. Similar RDFs to those discussed above were obtained for a DMPC membrane parametrised in the all-atom approximation [26].…”
Section: Chain Packing In the Hydrophobic Coresupporting
confidence: 78%
“…23 Initial well-equilibrated coordinates for the bilayer and GROMACS24 format united-atom parameters were obtained from Dr. D. Peter Tieleman.25 To maintain consistency with the AMBER26 format PAT parameters, the GROMACS lipid parameters were then translated by hand into an AMBER force field format, and their partial charges were replaced with previously known RESP-style charges. 27 In preliminary lipid-only simulations (not shown here) using an NPT ensemble, we found that these charges gave an area per lipid that was closer to the experimental value than did the GROMACS format charges (61.5 vs 64 Å2). AMBER format parameters and starting geometries for PATs were derived by ab initio calculation of the PAT inter-ring torsion energy and implicit solvent replica exchange simulation of the decamer chains; the details of this derivation are reported elsewhere.28 , 29 The combined system was then constructed by placing either an EHPT or HPT decamer near one leaflet of the bilayer.…”
Section: Simulation Parameters and Coordinatessupporting
confidence: 52%
“…The system was slowly heated up to 323 K in the presence of progressively decreasing position restraints on the lipid atoms, over a total period of 0.27 ns. Equilibration was then carried out for 30 ns at 323 K. The need for such an extensive equilibration period is justified by the long timescales associated with the rotation of the lipids around their long axis and with the conformational relaxation of the lipid acyl chains [122]. The final configuration of this trajectory was used directly as initial configuration for the simulation of the bilayer in pure water at 323 K (for the corresponding simulation at 475 K, the temperature was first progressively increased over a time period of 0.24 ns).…”
Section: Molecular Systemsmentioning
confidence: 99%